Feminist avant-garde: art of the 1970s : the Sammlung Verbund Collection, Vienna - Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); Palais des beaux-arts (Bruxelles, Belgique); Mjellby konstmuseum; Hamburger Kunsthalle; Photographers' Gallery; Museum Moderner Kunst (Autriche); Sammlung Verbund.; Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); et al. (Prestel, 2016)
Featuring a wide variety of work from artists both well-known and under the radar, this dynamic book reveals how women artists reclaimed control of the feminine image in photography, video, and performance art. This book documents a tectonic change in the way women portray themselves in art. Historically, women were depicted as a projection of male fantasies, prejudices, and relationships. However in the 1970s, for the first time, female artists began collectively to investigate visual representations of their own selves. They studied their own bodies and created the prospect of determined feminine identities. Editor Gabriele Schor explores the Feminist Avant-Garde to emphasize the role that these artists played for the last four decades. The works are provocative, radical, poetic, ironic, angry, cynical and heartfelt. The artists shared a collective consciousness that reassessed, and even rejected, what came before, turning to new ways of expression in the fields of photography, performance, film, and video. The collection SAMMLUNG VERBUND founded in 2004 in Vienna focuses on the feminist art movement of the 1970s as one of the main areas and is with 500 works the largest collection with this emphasis. Included are works by Eleanor Antin, Cindy Sherman, Ana Mendieta, Nil Yalter, Ketty La Rocca, Birgit Jürgenssen, Renate Bertlmann, Francesca Woodman and others. This important book emphasizes the accomplishments of women artists who have made a name for themselves while encouraging the young generation.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; biographie; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Comment être artiste, femme et autochtone au Canada ? Du stigmate à son renversement dans l'art contemporain - Goyon, Marie (Sociologie de l'Art, 2011)
Résumé Cet article analyse les usages de savoir-faire genrés dans la création contemporaine autochtone canadienne. Ils sont considérés dans leur caractère doublement situé, culturel et sexué. Comment analyser les usages des savoir-faire dits « féminins » (couture, broderie) dans les œuvres de plasticiennes contemporaines ? La réflexion s’appuie sur l’étude des trajectoires biographiques et des œuvres de trois artistes canadiennes autochtones. Une double stigmatisation de ces artistes, marquée de stéréotypes ethniques et genrés, est repérée dans les conditions d’exposition de leurs œuvres en tant qu’autochtones (musées d’ethnologie) et en tant que femmes (musées locaux, statut non professionnel des créatrices). Leurs démarches pourront être qualifiées de postcoloniales, interrogeant les frontières normatives entre arts « majeurs » et arts « mineurs », ainsi que la place des arts « premiers » et des femmes créatrices dans l’histoire de l’art
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; art contemporain; art textile; artisanat; artistes autochtones; arts; arts textiles; canada; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; travaux d'aiguilles

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques